The Homo mimeticus and the need for a mimetic turn. Interview with Nidesh Lawtoo (Itinera, 2024)
The present interview with Nidesh Lawtoo (lecturer at the University of Lausanne, Johns Hopkins University and KU Leuven and holder of the ERC project re-titled Homo Mimeticus: Theory and Criticism from 2017 to 2022) wants to highlight the “broad” and “complex” character of mimesis. The guiding idea is that mimesis – understood not simply as a copy or representation of reality but rather as a drive that leads humans to imitate other humans – provides us with a rich, wide-ranging, and paradoxically original perspective to knowing ourselves better. Thus, in a constant confrontation with the Greek roots of the term and the reflections of some modern and contemporary philosophers, the interview intends to clarify the scope and breadth of that mimetic turn proposed by Lawtoo in contemporary aesthetical debate.
Keywords: Mimesis, Mimetic Turn, Homo mimeticus, mimetic unconscious.